2017
DOI: 10.1007/s12291-017-0636-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Onion Consumption on Prevention of Nonalcoholic Fatty Liver Disease

Abstract: It is well known that dietary intakes play a pivotal role in pathogenesis of nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH); however, the role of each component of diet has not yet been elucidated. Our objective was to evaluate the effects of onion consumption on prevention of NAFLD/NASH development. Sprague-Dawley rats were fed either high-fat, high sugar diet (model group), or high-fat, high sugar diet plus 7% onion powder (model + onion), or chow diet ad libitum for 7 weeks. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
(26 reference statements)
5
24
0
Order By: Relevance
“…Plasma total protein and albumin reduced significantly in the metabolic syndrome control rats in comparison to normal rats. The present results coincide with those of Emamat et al. (2018) and Mohammed et al.…”
Section: Resultssupporting
confidence: 92%
“…Plasma total protein and albumin reduced significantly in the metabolic syndrome control rats in comparison to normal rats. The present results coincide with those of Emamat et al. (2018) and Mohammed et al.…”
Section: Resultssupporting
confidence: 92%
“…Several studies have also shown beneficial effects of regular onion consumptions in the prevention and/or treatment of several disease conditions in pre-clinical and clinical settings. For example, regular onion powder consumption (7% w/w for 7 weeks) in rats prevented the development of non-alcoholic fatty liver disease and its beneficial effects seemed to be, at least in part, mediated through reduction of the serum levels of alanine aminotransferase, triglycerides, and glucose, hepatic TNFα levels, and lower hepatic stenosis and lobular and portal inflammation [ 17 ]. Furthermore, another study reported that consumption of red wine extract of onion juice, by hypercholesterolemic individuals (250 ml daily for 10 weeks) significantly reduced total cholesterol and low density lipoprotein levels, and the inflammatory marker factor VII suggesting a cardio-protective roles for onion in individuals with risk factors for the development of cardiovascular diseases [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of natural products has gained attraction recently in many disease conditions due to their efficacy and relatively acceptable side effect profile. They showed beneficial effects in various conditions like non-alcoholic fatty liver [ 17 ], coronary artery diseases [ 18 ], hypertension [ 19 ], as well as in gallbladder cancer [ 20 ]. Allium cepa L. (Family Amaryllidaceae) is considered one of the most commonly used medical plant species in traditional medicine in the management of various conditions including that of inflammatory nature such as asthma [ 21 24 ] and recently in IBD [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that nutrition and dietary supple-ments play a pivotal role in the treatment of NAFLD (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Contextmentioning
confidence: 99%